A pilot study to compare auditory and visual reaction time in male and female young adults - Sachin Kadathanalu Shankaregowda; Praveen Shenoy; Santosh Kumar Bhise; Nikhil Rajak; Goothy, Sai Sailesh Kumar; Anita Choudhary; Rohit Singh Chouhan (Asian Journal of Medical Sciences, 2022)
Background: It was explained that there are very few studies that exist in the literature that assessed the reaction time in young adults. Aims and Objectives: The primary objective of the present study was to assess and compare the auditory and visual reaction time among male and female young adults. The secondary objective was to compare auditory and visual reaction time’s right- and left-hand responses. Materials and Methods: A total of 120 male and female young adults were part of the study after obtaining informed consent. Auditory and visual reaction time was assessed using the RT apparatus manufactured by Anand Agencies, Pune. The instrument can assess visual reaction time for the green and red light and auditory reaction time for tone and click sounds of both right- and left-hand responses. Results: Age and weight were significantly different between males and females, whereas height was not significant. The auditory and visual reaction times were not significantly different between the male and female participants. Conclusion: The present study reveals that there is no significant difference between the auditory and visual reaction time among male and female young adults. There is a need for more detailed studies to testify to the results.